Incidence of urinary tract infection (UTI) among pregnant women in Al-Muthanna Province - kadhim, Taisir Abdulelah (Al-Qadisiyah Journal of Pure Science, 2017)
This study reported the incidence of urinary tract infections (UTIs) among 64 pregnant women (50 patients and 14 controls) conducted in AL-Samawa Teaching Hospital of Gynecology and Pediatrics, as well as the isolation and identification of the pathogens of the same 510 Í¯responsible for the infection. Significant bacteriuria is defined as greater than 1bacteria per milliliter of urine. A total of 64 clean voided mid-stream urine samples were collected from pregnant women between the ages of 13-40 years. The results showed that the incidence of UTIs in this study population was 66%, and 33 bacterial isolates (20 single cultures and 13 mixed cultures) were identified based on colonial size, color characteristics, according to HiCrome UTI agar. The most predominant bacterium was Staphylococcus aureus (ATCC 25923) 12 (36.4%). This was followed by Enterococcus faecalis (ATCC29212) 4 (12%), Pseudomonas aeruginosa (ATCC 27853) 2(6), Klebsiella pneumonia (ATCC 13883) 1 (3%), Escherichia coli (ATCC 25922) 1 (3%), and a mixed culture of Enterococcus faecalis (ATCC 29212) and Staphylococcus aureus (ATCC 25923) 8(24.2%), Escherichia coli (ATCC 25922) and Enterococcus faecalis (ATCC 29212) 2(6%), Staphylococcus aureus (ATCC 25923) and Klebsiella pneumonia (ATCC 13883) 2(6%) , Enterococcus faecalis (ATCC 29212) and Klebsiella pneumonia (ATCC 13883) 1(3%) . All bacterial species exhibited 100% susceptibility to Amikacin and Imipenem whereas showed 100% resistance to Ampicillin, Erythromycin, Cephalothin, Cephalexin, Augmentin, Kanamycin, Tobramycin, and Neomycin